Childhood Teasing Experiences and Adult Emotional Distress: The Mediating Role of Social Anxiety and Self-Esteem - Vasiliki Varela; Kyriaki Gavrielidou; Despina Savidou; Meropi Simou; Gregoris Simos (Psychiatry International, 2025)
Previous research consistently identified depression and anxiety as leading contributors to the global disease burden. Recognizing risk and protective factors that lead to or guard against negative mental health outcomes therefore remains a research priority. The present study examined mediation models for the often-cited association between childhood verbal victimization and adult depression and anxiety symptomatology. Specifically, we investigated whether memories of childhood teasing related to adult adverse mental health outcomes indirectly via the mediated effects of self-esteem and social anxiety. Three hundred sixty-four (64.8% female) adult participants took part in a retrospective study by completing the Teasing Questionnaire—Revised; epidemiological scales of depression, anxiety, stress, social phobia, and social interaction anxiety; and a self-esteem measure. Memories of childhood teasing were indeed positively related to depression, anxiety, stress, social interaction anxiety, and social phobia scores and negatively related to current self-esteem, i.e., the individual’s subjective evaluation of their worth. Self-esteem and recalling being teased for one’s social skills were consistent predictors across all adult outcomes (depression, anxiety, stress, social anxiety, and social phobia). Lastly, self-esteem was found to be a partial mediator of the relationship between the memories of childhood teasing and depression and anxiety in adulthood, while social interaction anxiety partially mediated the relationship between teasing and anxiety, but not depression. These findings highlight the long-term psychological impact of childhood teasing and underscore the critical role of self-esteem and social anxiety as pathways through which early verbal victimization contributes to adult mental health outcomes, emphasizing the need for targeted interventions to foster resilience and mitigate lasting effects.